Balance Scorecard Sebagai Alat Ukur Kinerja Perusahaan (Studi Pada PT Sucofindo Timika) - Ignasius Narew; Dwi Idhan Putra (Journal of Financial and Tax, 2022)
This study aims to analyze the performance of PT Sucofindo Branch Timika measured using the concept of the Balanced Scorecard and to carry out strategic planning that must be applied to each perspective in the Balanced Scorecard to match the company's vision and goals. This research uses a descriptive method. The results showed that the company's performance was classified as good from the four perspectives of the Balanced Scorecard. In addition, for future strategic planning based on Importance Performance Analysis, companies need to re-evaluate the procurement of equipment that is not in accordance with customer needs and improve the quality of work results and the speed of the testing process. In addition, the company must provide clear career paths for employees